Cloning, Expression, and Characterization of Xylanase G2 from Aspergillus oryzae VTCC-F187 in Aspergillus niger VTCC-F017. (12th March 2021) - Tuyen, Do Thi; Cuong, Nguyen Tien; le Thanh, Nguyen Sy; Thao, Nguyen Thi; Hoang, Le Thanh; Trang, Nguyen Thi Hien; Trung, Nguyen Thi; Anh, Dao Thi Mai
Abstract : The study focuses on engineering of recombinant Aspergillus niger to produce highly active xylanase. The xylanase G2 encoding gene originating from Aspergillus oryzae VTCC-F187 was cloned, amplified, and inserted into the pAN7.1GluA vector with specific primers possessing Bam HI. The recombinant plasmid was introduced into Aspergillus niger VTCC-F017 by chemical methods. The recombinant strain was checked by polymerase chain reaction method and Southern blot. Next, the recombinant protein was expressed and purified by His-tag column. The molecular mass of the purified xylanase G2, as determined by sodium dodecyl sulphate polyacrylamide gel electrophoresis (SDS-PAGE), was 21 kDa with a specific activity of 1025 IU/mg towards 0.5% (w/v) of birchwood xylan. The optimal temperature and pH were 55°C and pH 6.5, respectively. The enzyme was stable in a temperature ranges 25–40°C and a pH ranges 5–7. The presence of Tween 80 enhanced xylanase activity. Triton X-100, however, had no impact on the function of the enzyme. The xylanase activity was reduced by Tween 20, SDS, and organic solvents. The enzyme was completely inhibited by Hg 2+ and partially by Zn 2+, Fe 2+, and Ag +, while it was slightly stimulated by K + and EDTA.